THE EFFECT OF YTTRIUM ADDITION ON CYCLIC OXIDATION RESISTANCE OF Fe-14Ni-9Al-7,5Cr ALLOY AT 800, 900, AND 1000ᴼC - AHMAD JAMIL (NIM : 12514059), FAQIH
The increase in population, technological advancement and economic growth, drive an increase in world’s electricity demand. The electricity demand is projected to increase upto 25% by 2040. In Indonesia, the electricity demand increased 8.6% annually through 2025. Advanced-ultra supercritical coal-fired boiler technology, operating at 35 MPa steam pressure and steam temperature 760oC, is being developed in order to obtain steam powered power plant’s efficiency up to 47%. To obtain such conditions, it is necessary to develop alloys that have good performance in that environment. In this study, yttrium was added in the Fe-14Ni-9Al-7,5Cr superalloy to study its effect on cyclic oxidation resistance. A series of experiments were conducted to study the oxidation resistance cyclic in Fe-14Ni-9Al-7,5Cr alloys with the addition of 0.1; 0.5 and 1% yttrium at temperatures of 800, 900, and 1000oC. The experiment began with weighing alloy materials according to the composition, then melted in a mini DC Arc Furnace. The alloy was then homogenized at 1100°C for 24 hours using an inert tube furnace. The test was done using a muffle furnace for 50 cycles with one cycle is one hour of heating in the furnace and 15 minutes of air-cooling. After the test, the change in alloy mass data perarea then calculated. Furthermore, the alloys were characterized using optical microscope, XRD, and SEM-EDS. From the results of characterization obtained, then analyzed microstructure, the oxide layer formed and the distribution of its elements Based on the research that has been done, it is found that the higher the oxidation temperature and the more percentage of yttrium added, the oxidation resistance of the alloy is reduced. The addition of yttrium promoting the growth of oxide become thicker. Addition of yttrium above 0.5% causes fast-growing oxides that are prone to spalling. Oxides formed after oxidation are Al2O3, Fe3O4, Fe2O3 and Cr2O3 at the addition of 0.1; 0.5 and 1% Y at 800, 900 and 1000oC. In addition to high yttrium, it encourages the growth of Al2O3 to consume Al in matrix and precipitate. The addition of yttrium did not significantly affect the distribution of Fe, Ni, and Cr elements.